REMEDIASI MISKONSEPSI SISWA DIKAJI DARI GAYA KOGNITIF DALAM MATERI BILANGAN BULAT DI SMP - Manora, Elsa; T, Ahmad Yani; Sayu, Silvia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study was aimed at 1) Describing the misconceptions of students towards the Field Independent and Field Dependent cognitive styles on integer operation material in class VII and 2) Describing whether or not misconceptions could be solved through remediation on cognitive style students in Independent Field and Field Dependent cognitive styles. This research applied a descriptive qualitative case study. The subjects in this study were class VII F students of SMP Negeri 4 Sungai Raya choosen by applying simple random sampling. The data collection techniques used in this research were 1) test methods in which it consisted of Group Embeded Figure Test (GEFT) and Multiple Choice test with open reasoning, 2) interview method which was conducted to Field Independent and Field Dependent students who had misconceptions, 3) remediation methods (metode pengajaran ulang/perbaikan) of the integer material. Based on the results of data analysis, it was obtained changes in the score of pretest and posttest. The mean score of students' pre-test was 37.91 and the mean scores of students' posttest was 96.7. This indicates that the score of the post-test after remediation increased and misconceptions that occured while doing the pretest had been minimized, there could not even be found any subjects that had misconceptions anymore and it means that the remediation (pengajaran ulang/perbaikan) given by the researcher successfully helped solve the misconceptions in integer operation material. Keywords: Cognitive Style, Integer, Misconception, Remedition